Pengaruh Payment Gateway, Human Capital, dan Orientasi Kewirausahaan terhadap Kinerja Keuangan UMKM : Studi Empiris pada UMKM di Kota Pekanbaru, Riau - Yogi Irmaningsih; M. Rasuli; Donal Devi Amdanata (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine and analyze the influence of payment gateways, human capital, and entrepreneurial orientation on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Pekanbaru City, Riau. The study employed a quantitative approach using primary data collected through questionnaires distributed to 100 MSME owners selected through a multistage area sampling technique. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results indicate that payment gateways have a positive effect on MSMEs' financial performance by improving transaction efficiency and convenience. Human capital also has a positive effect, suggesting that the knowledge, skills, and experience of business owners contribute significantly to business success. In addition, entrepreneurial orientation positively affects financial performance through innovation, proactiveness, and risk-taking behavior. Simultaneously, these three variables contribute to improving the financial performance of MSMEs in Pekanbaru City.